Tarsal tunnel syndrome secondary to osteochondroma of the calcaneus: a case report - Won, Sung Hun (BMC Musculoskelet Disord, 2020)
BACKGROUND: Tarsal tunnel syndrome is an entrapment neuropathy that can be provoked by either intrinsic or extrinsic factors that compresses the posterior tibial nerve beneath the flexor retinaculum. Osteochondroma, the most common benign bone tumor, seldom occur in foot or ankle. This is a rare case of tarsal tunnel syndrome secondary to osteochondroma of the sustentaculum tali successfully treated with open surgical excision. CASE PRESENTATION: A 15-year-old male presented with the main complaint of burning pain and paresthesia on the medial plantar aspect of the forefoot to the middle foot region. Hard mass-like lesion was palpated on the posteroinferior aspect of the medial malleolus. On the radiological examination, 2.5 × 1 cm sized bony protuberance was found below the sustentaculum tali. Surgical decompression of the posterior tibial nerve was performed by complete excision of the bony mass connected to the sustentaculum tali. The excised mass was diagnosed to be osteochondroma on the histologic examination. After surgery, the pain was relieved immediately and hypoesthesia disappeared 3 months postoperatively. Physical examination and radiographic examination at 2-year follow up revealed that tarsal tunnel was completely decompressed without any evidence of complication or recurrence. CONCLUSIONS: As for tarsal tunnel syndrome secondary to the identifiable space occupying structure with a distinct neurologic symptom, we suggest complete surgical excision of the causative structure in an effort to effectively relieve symptoms and prevent recurrence.